Preventing Suicide Through Resilience: An Integrative Quranic Perspective - Sofia, Nanum; Hude, Darwis (Universitas Islam Indonesia, 2025)
The significant increase in suicide cases in Indonesia requires important attention from all parties. One of the efforts to prevent suicide is to develop resilience. This research aims to explore the noble potential of humans based on the Qur'an as a capital in developing resilience. This study conducts a literature study through a thematic interpretation of Quranic verses pertaining to human potential, resilience, and the trials faced by humanity, alongside an exploration of relevant scholarly journals. The results of this research find that the noble potential of humans is a protective factor, while the negative potential of humans is a risk factor that can lead individuals to life threatening actions. The concepts of resilience in the Qur'an include intelligence, excellence, freedom, responsibility, moral/ethical awareness, a God-given nature, and the willingness to improve oneself. This research recommends five important points: 1) building and honing resilience, 2) using Allah's perspective in interpreting adversity and suffering, 3) understanding life and the process of human creation comprehensively, 4) strengthening the God-given nature (hablu min Allah), and 5) strengthening family bonds. hese five recommendations can be implemented by strengthening aspects from personal, family, and educational institutions, both formal and non-formal.